Characteristics of Work Accident to Tobacco Farmers in Indonesia - Ledya Anggriani Hariyanto; Retno Purwandari; Alfid Tri Afandi (Nursing and Health Sciences Journal (NHSJ), 2021)
Tobacco farmers are individuals who are members of farming groups engaged in the cultivation of the agricultural sector in the form of tobacco. When carrying out tobacco cultivation activities, farmers are vulnerable to work accidents. The purpose of this research was to describe the characteristics of work accidents on tobacco farmers in Kalisat District, Jember Regency. The research design used descriptive quantitative. This research employed a purposive sampling technique, with a total of 97 tobacco farmers as respondents. The research data were collected through a demographic questionnaire and a work accident accident questionnaire. In the type indicator, it was found that 43.3% farmers often experienced incidents of being hit by immovable objects. In the object indicator, 36.1% farmers often experience accidents due to work equipment. In the indicator of the nature of the wound 26.8% farmers often experienced minor injuries and 9.3% stated that they always experienced these incidents. In the indicator of the location of the wound, farmers often experienced injuries on the hands, namely 36.1%. In the cause indicator, 66.0% farmers stated that they rarely use Personal Protective Equipment (PPE). According to the results of this study, work accidents among tobacco farmers in Kalisat District are still highly prevalent. This research will be utilized as a preventative and assessment tool for public health center in the application of UKK and for PPL to develop outreach activities in order to reduce the number of work accidents. Keywords: agricultural; tobacco farmer; work accidents; descriptive